Proteomic and metabolomic integration reveals the effects of pre-flowering cytokinin applications on central carbon metabolism in table grape berries - Olmedo, Patricio; Núñez-Lillo, Gerardo; Vidal, Juan; Leiva, Carol; Rojas, Bárbara; Sagredo, Karen; Arriagada, César; Defilippi, Bruno G.; Pérez Donoso, Alonso G.; Meneses, Claudio; Carpentier, Sebastien C.; Pedreschi, Romina; et al. (Elsevier, 2023)
Consumers around the world prefer high quality table grapes. To achieve higher quality traits at ripening, grapevine producers apply different plant growth regulators. The synthetic cytokinin forchlorfenuron N-(2-chloro-4-pyridinyl)-N'-phenylurea (CPPU) is widely used, its effect on grape quality is poorly understood. We hypothesized that the use of CPPU in pre-flowering can lead to changes in the metabolism that affects grape quality at harvest. Therefore, we investigated the role of CPPU applications on the quality of grapes by integrating proteomics and metabolomics. CPPU-treated grapevines showed a significant increase in berry size and firmness. Proteomic analyses indicated that CPPU-treated berries accumulated enzymes associated with carbohydrate metabolism, glycolysis, and tricarboxylic acid (TCA) cycle at harvest. Metabolomic analyses showed shifts in the abundance of compounds associated with carbohydrate metabolism and TCA cycle in CPPU-treated grapes. These findings suggest that CPPU applications modulate central carbon metabolism, improving grape berry quality.